Basic solution for three parallel non-symmetric permeable mode-III cracks in a functionally graded piezoelectric material plate - Liang, J. (Archives of Mechanics, 2009)
The behavior of three parallel permeable cracks with different lengths in a functionally graded piezoelectric material plane subjected to anti-plane shear stress loading was studied by the Schmidt method. The problem was formulated through the Fourier transform into three pairs of dual integral equations. To solve the dual integral equations, the jumps of displacements across the crack surfaces were directly expanded in a series of Jacobi polynomials. The results show that the stress and the electric displacement intensity factors at the crack tips depend on the lengths, spacing of the cracks and the material parameters. It is also revealed that the crack shielding effect is present in functionally graded piezoelectric materials.